Financial Literacy and Risk-Taking Propensity of Nepalese Undergraduates - Ghimire, Purushottam; Silwal, Sarita (SAIM Journal of Social Science and Technology, 2025)
Background: This study explores the influence of financial attitudes and financial knowledge on the risk-seeking tendencies of Nepalese undergraduate students, grounded in behavioral finance theories, notably Prospect Theory and Human Capital Theory. Objective: To examine how financial knowledge and mindset shape students’ financial attitudes and their propensity for financial risk-taking. Methods: A cross-sectional quantitative research design was utilized, surveying 513 undergraduate students from various colleges in Kathmandu Valley using purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) to test hypothesized relationships among variables. Results: Findings indicate that financial knowledge positively impacts both financial behavior and risk-taking propensity. Moreover, financial behavior serves as a strong partial mediator between financial knowledge and risk-taking tendency. Conclusions: The results underscore the importance of integrated financial education programs that enhance both cognitive knowledge and behavioral skills to support sound financial decision-making among youth. This study expands the literature on financial literacy in emerging economies and provides valuable insights for policymakers aiming to reform financial education frameworks.